PENGARUH WORKLIFE BALANCE DAN SELF EFFICACY TERHADAP KINERJA PEGAWAI KANTOR CAMAT LANGSA LAMA - Aulia Fahrul Azmi; Dewi Rosa Indah; Dhian Rosalina (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This inquiry endeavors to dissect the interrelationship between Work–Life Balance and Self-Efficacy as predictive determinants of employee performance within the administrative framework of the Langsa Lama District Office. The investigation adopts a descriptive, quantitative paradigm, engaging the entire population of thirty civil servants through a saturated sampling design. Empirical data were elicited via triangulated methods, structured observation, dialogic interviews, and standardized questionnaires, and subsequently processed using multiple linear regression analysis facilitated by SPSS (v.25). Findings demonstrate that equilibrium between occupational and personal domains (Work–Life Balance) exerts a positive and statistically significant influence on performance indices. Similarly, Self-Efficacy manifests a comparable directional effect, indicating that employees’ confidence in their own competencies serves as a vital catalyst for optimal productivity. Jointly, these two psychological constructs elucidate 47.2% of the variance in performance outcomes, affirming that harmonized life domains and robust self-belief synergistically cultivate higher levels of institutional efficacy.